Individual Counselling with Cognitive Behavior Therapy to Reduce Immunization Needle Fear in Elementary Students - Indriyansyah, Meezy; Netrawati (Bisma The Journal of Counseling, 2025)
School-age children during their developmental stage should maintain their health status through immunization. For children, receiving vaccinations is one of the terrifying experiences in life since needles are used to administer the shots. Needle fear during immunization often occurs in children because children feel that needles will give unbearable pain, hurt, and give harmful side effects. This study aimed to determine the effectiveness of individual counselling services with cognitive behavior therapy (CBT) in reducing elementary school students' needle fear. Using a single subject research design, with purposive sampling method, this research assesses the effectiveness of CBT individual counselling on 3 students. The results of this study obtained the level of needle fear on elementary school students n = 3 at a very high level (mean = 82.85%) after being given CBT individual counselling the needle fear level were decreasing very low level (mean 7.14%). CBT individual counselling has benefited in various types of mental health problems. CBT Individual counselling encourage new thoughts, feelings and behaviors for children with needle fear. It is important for primary school students to be given individual counselling cognitive behavior therapy in order to prepare students to the immunization syringe and to improve negative perceptions through counselling so that immunization outcomes in primary school students can be achieved optimally.